The Effect of Apple Vinegar Addition on the Quality and Shelf Life of Cooked Sausage during Chilling Storage - Anna Okoń; Dorota Zielińska; Piotr Szymański; Anna Łepecka; Urszula Siekierko; Katarzyna Neffe-Skocińska; Monika Trząskowska; Katarzyna Kajak-Siemaszko; Barbara Sionek; Marcelina Karbowiak; Danuta Kołożyn-Krajewska; Zbigniew J. Dolatowski (Applied Sciences, 2024)
As more and more consumers are becoming conscious of the safety and taste of meat products, the use of natural additives and innovative processing techniques has gained significant attention. Naturally fermented fruit vinegar is rich in organic acids and antioxidant phenolic compounds. In addition, it contains amino acids, minerals, vitamins, and provitamin beta-carotene, and the presence of acetic acid bacteria may have a positive effect on consumer health. The study aimed to assess the impact of different concentrations of apple vinegar addition on the quality of cooked sausage, focusing on physicochemical parameters, including fatty acid profile and oxidative stability, as well as microbiological quality and sensory changes after production and during chilling storage. Four variants of sausage were prepared: C—sausage without apple vinegar; V1—sausage with 1% of apple vinegar; V3—sausage with 3% of apple vinegar; and V5—sausage with 5% of apple vinegar. All of the tests were carried out after production, as well as after 7 and 14 days of refrigeration storage. The addition of apple vinegar decreased the pH value and increased the oxidation-reduction potential and lipid oxidation in the samples V1, V3, and V5. The sausage with the 5% addition of apple vinegar (V5) was characterized by significantly more intensive brightness (parameter L* = 54.67) in comparison to the C sample (parameter L* = 52.78). The sausages that were tested showed good microbiological quality concerning the total number of microorganisms, lactic acid bacteria, and the absence of pathogenic bacteria. The addition of apple vinegar contributed to the reduction in the intensity of the cured meat flavor and the fatty flavor. Therefore, according to the results presented in this work, it can be concluded that 3% of vinegar is the optimal addition, which may be used in the next step of investigation, taking into account color formation abilities as well as microbiological quality and lipid oxidation processes.